"Governance restricts": A contextual assessment of the wastewater treatment policy in the Guadalupe River Basin, Mexico. (August 2017) - Casiano Flores, Cesar; Özerol, Gül; Bressers, Hans
Abstract: Lack of wastewater treatment is among the main water problems worldwide. The implementation of wastewater treatment policies faces varying challenges given the many different contexts. Therefore, context-sensitive approaches are required from a governance perspective. This paper aims to improve the understanding of the role of contextual factors in water and wastewater governance drawing on empirical evidence from Latin America, with a focus on the Guadalupe River Basin in Mexico. The findings indicate that the governance context restricts the implementation of wastewater treatment policy. Thus, future reforms should consider the top-down nature of the policy implementation process. Highlights: The River Basin Commission has no influence on the wastewater treatment policy implementation. Water utilities at the municipal level lack the capacity to implement the wastewater treatment policy. Top-down and bottom-up implementation processes do not support each other. The governance context restricts the top-down and bottom-up implementation processes.